Analisis Kinerja dan Keberlanjutan Implementasi Usaha Minuman Inovasi Susu Kedelai di Kota Palembang - Lienatha, Audrey Rose; Fernando, Vicente Luis; Kasih, Yulizar (MDP Student Conference, 2025)
This study analyzes the financial performance, customer satisfaction, and sustainability of Gao Xing Cha, a soy milk-based beverage business. The research employs a quantitative descriptive method using data collected from customer questionnaires and financial reports. The findings indicate revenue fluctuations, with a significant increase during offline promotions, followed by a decline afterward. This suggests the need to strengthen digital marketing strategies to maintain sales stability. The majority of customers are students, with Brown Sugar Soy Milk Tea being the most popular variant. Additionally, packaging and financial record-keeping require improvement to enhance competitiveness and profitability. By optimizing marketing strategies and improving operations, Gao Xing Cha has the potential to strengthen its sustainability in the soy milk-based beverage industry.